Analysis Of Waste Cost Behavior In Environmental Accounting Of Enrekang General Hospital, Enrekang Regency - Yasri Tarawiru; Rika Rahma; Dapianti Yunus (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
Hospitals within the community have a legitimacy to move freely in carrying out their activities, but over time because the company's position becomes very vital in people's lives, the impact will also be very large. Environmental accounting is a development of social accounting as a form of social responsibility in the field of accounting which functions to identify, recognize, measure, present, and disclose environmental accounting. This study aims to determine the cost behavior applied to the Massenrempulu General Hospital, Enrekang Regency with PSAK No.33 revision 2011. The data collection techniques used in this research are field studies, documentation, and interviews. Informants in this study were WWTP staff at Massenrempulu General Hospital. Data analysis techniques in this study used data reduction, display, and drawing conclusions or data verification. The results of the study show that several environmental accounting cost treatments are not in accordance with PSAK, for example recognition and measurement are in accordance with PSAK and identification, presentation and disclosure are not in accordance with PSAK. Then the presentation and reporting for Presentation of environmental costs is presented in the form of hospital operational reports while the reporting is included in the financial statements.